What’s the key for success? Translocation, growth and thermal stress mitigation in the Mediterranean coral Cladocora caespitosa (Linnaeus, 1767) - Roveta, Camilla; Coppari, Martina; Calcinai, Barbara; Di Camillo, Cristina Gioia; Marrocco, Teo; Pulido Mantas, Torcuato; Puce, Stefania; Torsani, Fabrizio; Valisano, Laura; Cerrano, Carlo (Frontiers in Marine Science, 2023)
Marine heat waves (MHWs) are affecting corals populations, advocating their inclusion in restoration actions since conservation measures may be not sufficient. Cladocora caespitosa is a Mediterranean reef-building, long-living species, with low recruitment rate and high juvenile mortality, leading to the need for its inclusion in international and European legislations. The aim of this study, conducted in the southern Tyrrhenian Sea, was to test the translocation of several C. caespitosa colonies thriving on an artificial substrate intended for demolition, applying transplantation techniques. Thirty-four colonies were transplanted in May 2018, and monitored over 4 years, to check for their persistence and health status. The shaded position of the recipient site resulted adequate, considering that colony survival rates were as high as 82.4%, 70.6% and 55.9% in October 2018, January 2020 and October 2022, respectively. Colonies presented signs of suffering only after the high temperatures occurred during summer 2022, with a decreasing rate of -2.5 ± 0.4 corallite/month. To better interpret the documented survival rates, 40 fragments of C. caespitosa were reared in aquaria to test temperature and light effects on growth rates and resistance to thermal stress, simulating a MHW and exacerbating the dim-light natural conditions of the recipient site, exposing half of the fragments to complete darkness. Only bigger fragments produced new corallites, with a rate of 1.3 ± 0.3 corallites/month, like the natural growth rate obtained in the field before the thermal anomaly, highlighting the suitability of ex-situ rearing as a potential tool to supply restoration project. After 5-days at 28.5°C, all fragments survived, despite showing tissue retraction, shorter tentacles, lower responsiveness, and zooxanthellae density variation. Overall, our results highlighted a promising plasticity of C. caespitosa in the field, representing a good candidate for restoration purposes. In aquaria this adaptive potential has been tested on a single genotype and more tests are needed to assess the intraspecific variability of these responses. A first insight into the species-based siting selection was provided to ensure the success of a restoration action. Our results point out the importance of knowing life history traits and ecological optima to design proper management and restoration measures.